DETERMINAN NON PERFORMING LOAN PADA BANK PEMBANGUNAN DAERAH DI INDONESIA - Febri Nanda Marchela (2023)
Macroeconomic as well as microeconomic conditions often affect the financial and banking sectors. This study aims to determine the effect of microeconomic and macroeconomic variables consisting of BOPO, ROA, money supply, and unemployment rate on Non-Performing Loans (NPL) of Regional Development Banks in Indonesia. The sampling technique used is purposive sampling technique. With this sampling technique, 20 Regional Development Banks in Indonesia were selected for the period from 2008-2021 so that the number of observers in this study was 280 data. The data is obtained from the annual reports of the Regional Development Bank, Bank Indonesia, the Central Bureau of Statistics (BPS) and the Financial Services Authority (OJK). The data processing method used is panel data regression with the selected model, namely the fixed effect model. The results showed that BOPO, ROA, the money supply, and the unemployment rate had a significant positive effect on the NPL of Regional Development Banks.